Designing a Shopping Mall in Ciputat, South Tangerang - Rifky, Asmara Aditia (Institut Seni Indonesia Bali, 2025)
The city of South Tangerang, Banten Province, Indonesia has various potentials that can be developed and become a source of income for the South Tangerang region. Ciputat in South Tangerang has experienced a transformation in the development of modern shopping centers. The aim of this study is to design a shopping mall in Ciputat. The method used is a futuristic architecture which is related to technological developments, increasingly developing, creative and innovative. Combining the technological development process in shopping malls, namely uniting the concept of expression in the structural system with the mall building, ensuring sustainability, comfort and visitor satisfaction and also the shopping center as well as being a place for refreshing or entertainment. The establishment of a shopping center in South Tangerang City cannot be separated from the increasing population of the population in Ciputat, South Tangerang. Shopping malls provide shopping experiences and tourist destinations or entertainment facilities that are comfortable and enjoyable for visitors, as well as creating employment opportunities that can provide useful employment opportunities for local residents in the Ciputat area of South Tangerang City.